(untitled) (Indian Journal of Integrative Medicine, 2024)
Folliculitis, an inflammatory condition affecting hair follicles, is often caused by bacterial or fungal infections. In the realm of conventional medicine, the treatment of folliculitis typically involves a range of pharmaceutical options. Depending on the severity and underlying cause, healthcare professionals may prescribe topical or oral antibiotics, antifungal medications, or antiviral drugs to target the specific infection responsible for the condition, but there is growing interest in complementary therapies, such as homoeopathic medicine, due to their holistic approach. This case report details the treatment of a 20-year-old male with recurrent, painful folliculitis on his face and scalp, which had shown limited response to conventional treatments. After a thorough homoeopathic assessment, the patient was prescribed Sulphur 30C. Over the course of several weeks, the patient experienced a notable reduction in the frequency and severity of folliculitis outbreaks, without any adverse side effects. The patient reported high satisfaction with the treatment, as measured by the ORIDL scale. This case highlights the potential of homoeopathic medicine as an effective and personalized treatment for folliculitis, especially for patients who do not respond well to traditional therapies. The positive outcome suggests that homoeopathy could be a valuable and safe option for managing folliculitis. Nonetheless, further research and larger studies are necessary to thoroughly evaluate the efficacy and safety of homoeopathic treatments in various dermatological conditions. This research will enhance the understanding of homoeopathy’s role in dermatological care and aid in making informed treatment decisions for patients seeking alternative options also exploring the adjunct scope for homoeopathy.